Relaciones lingüísticas entre el sardo y el italiano - Mª Carmen, BARRADO BELMAR (Revista de Filología Románica, 2002)
In this study the situation of the sardinian language throught history is examined, as well as its relationship with italian. Attention is paid to the three periods of the italianization, wich begins with the pisan and genovese influences (centuries XI to XIX), being followed by the stage of the House of Savoy and by the situation going from year 1861, date of the National Unification, until the present time, in which there is a linguistic living together but with a level-dependent differentiation of use.